A comparative study using supervised learning for anomaly detection in network traffic. Issue 1 (1st January 2022) - Garg, R; Mukherjee, S
Abstract: A user connects to hundreds of remote networks daily, some of which can be corrupted by malicious sources. To overcome this problem, a variety of Network Intrusion Detection systems are built, which aim to detect harmful networks before they establish a connection with the user's local system. This paper focuses on proposing a model for Anomaly based Network Intrusion Detection systems (NIDS), by performing comparisons of various Supervised Learning Algorithms on metric of their accuracy. Two datasets were used and analysed, each having different properties in terms of the volume of data they contain and their use cases. Feature engineering was done to retrieve the most optimum features of both the datasets and only the top 25% best features were used to build the models – a smaller subset of features not only aids in decreasing the capital required to collect the data but also gets rid of redundant and noisy information. Two different splicing methods were used to train the data and each method showed different trends on the ML models.